As-Built Analysis - An Integral Part Of Pile Foundation Design - Dan Yang (Deep Foundations Institute, 2010)
Pile foundation designs are performed routinely based on geotechnical information available at the time of design, often with due consideration of large uncertainties inherent to soils and site conditions. These uncertainties frequently are the causes of piles being installed not the same as those designed, especially by factors beyond quality assurance and quality control. With a variety of both satisfactory and unsatisfactory pile test results from these nonconforming piles, the design engineers are required to examine the foundation performance as a whole against the project design requirements before signing off on them or calling for potentially costly remediation. Over the years, as-built analysis has been a consistent way of dealing with pile non-conformity and damage in our practice, avoiding many construction delays and it is an integral part of our pile foundation design. In this paper, the key elements of an as-built analysis along with several major bridge projects are presented.